Peran Haji Mohammad Syoedja’ bagi Perkembangan Penolong Kesengsaraan Oemoem (PKO) Muhammadiyah di Yogyakarta (1920-1931) - Atsna Ikmalia Pasa (JSI: Jurnal Sejarah Islam, 2022)
This study aims to determine the biography of Haji Mohammad Syoedja' and his role in the development of PKO Muhammadiyah in Yogyakarta in 1920-1931. This study uses a historical method that focuses on literature review. The sources used in this study include books, journals, newspaper archives, and document archives which were analyzed using descriptive analysis methods. While the approach used in this research is a historical and sociological approach. This research uses role theory (Soejono Soekanto) and social movement theory (Sidney Tarrow). The results of this study are; First, Haji Mohammad Syoedja' is the son of Haji Hasyim, a lurang of the Yogyakarta palace, who was born on August 2, 1882. Since childhood, Haji Mohammad Syoedja' has been close to K.H. Ahmad Dahlan as his student. Haji Mohammad Syoedja' became the founder and first chairman of the PKO Muhammadiyah. Second, Haji Mohammad Syoedja' during his time as chairman of the PKO Muhammadiyah had several important roles including; pioneered the establishment of PKO Muhammadiyah in 1918, established various social services such as hospitals, poor houses, and orphanages, contributed his thoughts, energy and materials for the benefit of the PKO section, established relationships and expanded networks and introduced PKO Muhammadiyah to the general public.